2012
DOI: 10.1590/s0103-50532012000100004
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical applications of nanobiosensors: the state-of-the-art

Abstract: O desenvolvimento de nanobiosensores é um dos avanços mais recentes no campo da nanotecnologia. A investigação sobre nanobiosensores ópticos com dimensões submicrométricas tem aberto novos horizontes para as medições intracelulares. Aproveitando as propriedades únicas dos nanomateriais, nanobiosensores mais rápidos e sensíveis podem ser desenvolvidos. Além de serem sensíveis e rápidos, os estudos de nanobiosensores têm voltado seus esforços para o desenvolvimento de sensores baseados em nanomateriais que são a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 98 publications
(125 reference statements)
0
19
0
1
Order By: Relevance
“…Some nanodiagnostic tools are based on nanomaterials such as liposomes, nanopores and nanowires, which are coupled to conventional methods such as fluorescence, potentiometry and voltammetry. 16 Most of them include enzyme-linked immunosorbent assay (ELISA) and reverse transcriptase polymerase chain reaction. Although these systems give rapid diagnostic information and use of inexpensive materials, they are currently unavailable or are scarce for clinical practice.…”
Section: Nanobiosensorsmentioning
confidence: 99%
“…Some nanodiagnostic tools are based on nanomaterials such as liposomes, nanopores and nanowires, which are coupled to conventional methods such as fluorescence, potentiometry and voltammetry. 16 Most of them include enzyme-linked immunosorbent assay (ELISA) and reverse transcriptase polymerase chain reaction. Although these systems give rapid diagnostic information and use of inexpensive materials, they are currently unavailable or are scarce for clinical practice.…”
Section: Nanobiosensorsmentioning
confidence: 99%
“…Nanobiosensors systems are efficiently used in diagnosis of diseases, environmental monitoring, food quality control, and defense as a smart approach (Zhou et al, 2011;Rai et al, 2012;Singh et al, 2014). For instance, by using goldcoated nanobiosensors, Duman et al (2009) demonstrated detection of target molecules (synthetic and PCR products) very effectively at nanomolar levels.…”
Section: Role Of Nanobiosensors In Diagnostics Of Tbmentioning
confidence: 99%
“…These immunosensors were applied for phage detection, resulting in great potential in health care, with special emphasis on food safety (Shirale et al, 2010). It is known that applications of nanomaterials in biosensors provided opportunities to generate a new aspect of biosensor technologies and with importance in food analysis (Rai et al, 2012). It is known that applications of nanomaterials in biosensors provided opportunities to generate a new aspect of biosensor technologies and with importance in food analysis (Rai et al, 2012).…”
Section: Nanosensorsmentioning
confidence: 99%
“…Electronic noses were applied to the detection of fungal contamination of cereal grain samples, for food spoilage detection and for the presence of Ganoderma boninense on palm oil tree trunks (Abdullah et al, 2011 and reference there in). Electrochemical nanosensors, especially amperometric ones, are of great interest nowadays, because of their high sensitivity for the detection of important components or pollutants in agriculture and in foods Rai et al, 2012). Novel nanomaterial-based electrochemical sensors and biosensors, such as carbon nanotubes and metallic nanoparticles, among others, for pesticide detection in food have been reviewed recently and showed advantages over classical detection techniques (Xiang et al, 2011).…”
Section: Nanosensorsmentioning
confidence: 99%
See 1 more Smart Citation